Herbaceous plant ecology: Recent advances in plant ecology - Valk, A.G. Van der (Springer, 2012)
Presents an overview of advances in the ecology of various kinds of non-forested ecosystems (grasslands, deserts, and wetlands) on a variety of topics, including species diversity and the factors that control species diversity, impacts of disturbances (grazing, mowing, fire, flooding).